Tuberculous pericarditis in a 71-year-old immunocompetent patient: Case report - Carlos Mejia Irias; Odalis Cerrato; Estephany Díaz Mairena (IDCases)
Tuberculosis is a transmissible disease caused by the bacterium Mycobacterium tuberculosis. It is the leading cause of mortality due to infectious diseases. Tuberculous pericarditis is one of the manifestations of extrapulmonary tuberculosis and represents the primary cause of pericardial effusion in developing countries. We present the case of a 71-year-old male patient with a history of 1 month of dyspnea, accompanied by paroxysmal nocturnal dyspnea and unintentional weight loss. An echocardiogram revealed the presence of severe pericardial effusion, for which pericardiocentesis was performed, and the pericardial fluid was analyzed using the Xpert MTB/RIF test, which confirmed the presence of Mycobacterium tuberculosis without resistance to Rifampicin. This is a case of Tuberculous Pericarditis as the cause of pericardial effusion, in which the etiological diagnosis was made possible through molecular biological analysis of the pericardial fluid. The importance of disseminating such cases lies in emphasizing that, even in the 21st century, in developing countries like Honduras, it is crucial not to dismiss tuberculosis infection, as it remains the leading cause of pericardial effusion in endemic regions.